Continuous-time co-operation of integrated electricity and natural gas systems with responsive demands under wind power generation uncertainty - Nikoobakht, Ahmad; Aghaei, Jamshid; Shafie-khah, Miadreza; Catalão, J. P. S. (IEEE, 2020)
This paper studies the role of electricity demand response program (EDRP) in the co-operation of the electric power systems and the natural gas transmission system to facilitate integration of wind power generation. It is known that time-based uncertainty modeling has a critical role in co-operation of electricity and gas systems. Also, the major limitation of the hourly discrete time model (HDTM) is its inability to handle the fast sub-hourly variations of generation sources. Accordingly, in this paper, this limitation has been solved by the operation of both energy systems with a continuous time model (CTM). Also, a new fuzzy information gap decision theory (IGDT) approach has been proposed to model the uncertainties of the wind energy. Numerical results on the IEEE Reliability Test System (RTS) demonstrate the benefits of applying the continuous-time EDRP to improve the co-scheduling of both natural gas and electricity systems under wind power generation uncertainty.
Keywords: demand response program; continuous-time model; natural gas system; IGDT method; wind energy; fi=Sähkötekniikka|en=Electrical Engineering|